The impact of board size, ownership structure and characteristics of the supervisory board on the financial performance of listed companies in Vietnam - Phong Le, Hoang; Nguyen, Ba Hoang (Technium Business and Management, 2024)
This study focuses on examining the influence of board size, ownership structure and characteristics of the supervisory board on the financial performance of companies listed on the Vietnam stock market. Using the fixed-effects regression model (FEM) and the random-effects model (REM) with panel data from 2017 to 2021, the research results have shown: (i) ownership (share ownership ratio of major shareholders are state, foreign investors, domestic private investors, members of the board of directors) have a positive influence on financial performance, (ii) board size has a negative effect on the financial performance, and (iii) characteristics of the supervisory board has a positive effect on the financial performance of companies listed on the Vietnam stock market. Based on the research results, the authors propose several key policy recommendations to enhance the financial performance of listed companies on the Vietnam stock market.